2015
DOI: 10.1016/j.scitotenv.2014.08.082
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the origin of suspended sediment in a large Mediterranean river by combining continuous river monitoring and measurement of artificial and natural radionuclides

Abstract: Delivery of suspended sediment from large rivers to marine environments has important environmental impacts on coastal zones. In France, the Rhone River (catchment area of 98,000 km(2)) is by far the main supplier of sediment to the Mediterranean Sea and its annual solid discharge is largely controlled by flood events. This study investigates the relevance of alternative and original fingerprinting techniques based on the relative abundances of a series of radionuclides measured routinely at the Rhone River ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…These last authors report the major role of sedimentary rocks outcropping in the mountains (e.g. Furthermore, Zebracki et al (2015) used geogenic radionuclides as fingerprints of sedimentary masses transported during flood events to estimate that the Pre-Alpine tributaries (Durance, Ouvèze, Aigues, Figure 1) would account for 38 to 53% of the SPM flux delivered by the Rhône River. By using a model based on sedimentary mass balance, these authors estimated that the Durance River contributes 23 % of the SPM flux transported by the Rhône River.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These last authors report the major role of sedimentary rocks outcropping in the mountains (e.g. Furthermore, Zebracki et al (2015) used geogenic radionuclides as fingerprints of sedimentary masses transported during flood events to estimate that the Pre-Alpine tributaries (Durance, Ouvèze, Aigues, Figure 1) would account for 38 to 53% of the SPM flux delivered by the Rhône River. By using a model based on sedimentary mass balance, these authors estimated that the Durance River contributes 23 % of the SPM flux transported by the Rhône River.…”
Section: Discussionmentioning
confidence: 99%
“…By using a model based on sedimentary mass balance, these authors estimated that the Durance River contributes 23 % of the SPM flux transported by the Rhône River. Furthermore, Zebracki et al (2015) used geogenic radionuclides as fingerprints of sedimentary masses transported during flood events to estimate that the Pre-Alpine tributaries (Durance, Ouvèze, Aigues, Figure 1) would account for 38 to 53% of the SPM flux delivered by the Rhône River. In our study, the Durance River contribution to the SPM load of the Rhône River is estimated at 32% (Figure 7(B)), which agrees well with these previous estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Collins et al, 2010a;Evrard et al, 2011;Owens et al, 2000;Franz et al, 2013). The method has been used in a wide range of objectives, scales, types and number of sources, and tracer variables (Ben Slimane et al, 2013;Tiecher et al, 2015;Zebracki et al, 2015). This has led to the development of robust methods capable of defining potential tracers and of estimating sediment contributions from different sources with greater accuracy in mathematical terms, together with measures of the associated uncertainties.…”
Section: The Contextmentioning
confidence: 99%
“…However, radionuclides can also serve as effective geochemical indicators. They have been used to assess sedimentation rate (Allen et al, 1993), to trace material sources (Gulin et al, 2014;Zebracki et al, 2015), to evaluate soil erosion (Iurian et al, 2013;Martinez et al, 2009), to estimate soil heterogeneity with depth (Fujiyoshi and Sawamura, 2004), and even to reconstruct big river flood events (Yang et al, 2013). All these studies have demonstrated that variation in environmental radionuclides could reflect changes that had occurred in the soil or sediment.…”
Section: Introductionmentioning
confidence: 99%